Design and modelling of construction machinery - Yao, Ping (2016)
Rotary drilling rigs are big-sized massive machines. They are heavily used in the field of constructions of buildings and bridges in order to achieve the operational efficiency, safety and human protection. However, due to size and weight of such construction machines, there are some challenges such as difficulty in operations and controls, condition monitoring and autonomy, which allows room for research and development. The purpose of the project is to study the structure of a rotary drilling rig and create a 3D CAD model of it. The structure of the rig includes chassis, mast, Kelly bar and drill auger. Each structure has its own characteristics, like the telescopic mechanism of chassis, segmented folding of mast, and merits and demerits of friction and interlocking Kelly bar. There are four different construction methods: Continuous Flight Auger drilling, drilling with casing oscillator, drilling with casing drive adapter and drilling with diaphragm wall grab which applies to different geological conditions. The 3D CAD model of the rig was created by SolidWorks while the isometric projection and orthographic views were indicated. The degree of freedom of the rig is five. The power of rig is main hydraulic. The control of the drilling equipment was explained, and its remote control was discussed.